2014
DOI: 10.1038/nsmb.2799
|View full text |Cite
|
Sign up to set email alerts
|

The retrovirus HERVH is a long noncoding RNA required for human embryonic stem cell identity

Abstract: Human endogenous retrovirus subfamily H (HERVH) is a class of transposable elements expressed preferentially in human embryonic stem cells (hESCs). Here, we report that the long terminal repeats of HERVH function as enhancers and that HERVH is a nuclear long noncoding RNA required to maintain hESC identity. Furthermore, HERVH is associated with OCT4, coactivators and Mediator subunits. Together, these results uncover a new role of species-specific transposable elements in hESCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
370
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(398 citation statements)
references
References 26 publications
18
370
0
10
Order By: Relevance
“…We generally observed a greater propensity for the expression of LTR-associated lncRNAs in ESCs over more differentiated cells, consistent with the work of others (Kelley and Rinn 2012). Indeed, expression of endogenous retroviral elements is common in mouse and human ESCs and was postulated to contribute to species-specific regulation of pluripotency and differentiation (Macfarlan et al 2012;Lu et al 2014). It will be interesting to investigate loss of additional LTR-associated lncRNAs with respect to their contribution to the ESC gene expression program.…”
Section: Discussionsupporting
confidence: 75%
“…We generally observed a greater propensity for the expression of LTR-associated lncRNAs in ESCs over more differentiated cells, consistent with the work of others (Kelley and Rinn 2012). Indeed, expression of endogenous retroviral elements is common in mouse and human ESCs and was postulated to contribute to species-specific regulation of pluripotency and differentiation (Macfarlan et al 2012;Lu et al 2014). It will be interesting to investigate loss of additional LTR-associated lncRNAs with respect to their contribution to the ESC gene expression program.…”
Section: Discussionsupporting
confidence: 75%
“…An appropriate activation of these LTRs was shown to be essential for iPS reprogramming (Lu et al 2014;Ohnuki et al 2014). Depleting LTRs in ES cells led to cell differentiation (Fort et al 2014;Lu et al 2014), whereas augmenting LTRs impaired cell differentiation (Ohnuki et al 2014). Concordantly, we found that HCCs can be stratified according to LTR expression level and that LTR-high HCCs are less well-differentiated than LTR-low ones, confirming that an excess of LTR activity impairs cell differentiation.…”
Section: Discussionsupporting
confidence: 60%
“…The mechanisms of regulation of the LTRs was previously investigated in iPS and ES cells, which express high levels of specific LTR families, namely, LTR7 and HERVH. An appropriate activation of these LTRs was shown to be essential for iPS reprogramming (Lu et al 2014;Ohnuki et al 2014). Depleting LTRs in ES cells led to cell differentiation (Fort et al 2014;Lu et al 2014), whereas augmenting LTRs impaired cell differentiation (Ohnuki et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study by Lu et al showed that HERV-H activity regulated by OCT3/4 and p300 is important for generation and selfrenewal of iPSCs (20). Among OSKM reprogramming factors, we showed that KLF4 levels are the most important for activating and resuppressing LTR7s.…”
Section: Discussionmentioning
confidence: 78%